Efficacy of topiramate as add-on therapy in two different types of progressive myoclonic epilepsy. - Demir, Caner Feyzi; Ozdemir, Hasan Hüseyin; Müngen, Bülent (My University, 2013)
The present article describes two unrelated cases of progressive myoclonic epilepsy (PME) of the Lafora's disease and Unverricht-Lundborg types who were treated with topiramate (TPM) as add-on therapy for their myoclonus. After the initiation of topiramate therapy both cases responded with marked decrease in myoclonic seizure frequency and improvement of quality of life. Topiramate appears to be a useful alternative agent in cases of PME and could be consider for adjunctive therapy.
Keywords: Anticonvulsants; Drug Therapy, Combination; Female; Fructose; Humans; Myoclonic Epilepsies, Progressive; Young Adult; anticonvulsive agent; drug derivative; fructose; topiramate; article; case report; drug combination; female; human; myoclonus epilepsy; young adult